A study on the machining characteristics of specimens with spherical shape using laser-assisted machining. (5th May 2016) - Kim, In-Woo; Lee, Choon-Man
Highlights: Laser assisted machining (LAM) of specimens with spherical shape is performed. Contouring preheating method is proposed for the experiment. Specimens of AISI 1045, Inconel 718 and titanium alloy are used for the experiment. The depth of cut for the experiment is determined by finite element analysis. Effectiveness of LAM is verified by comparing with the conventional machining. Abstract: Materials such as nickel-based alloys have high strength and excellent resistance to many corrosive environments, and are widely used in various industrial fields, but are difficult to machine using conventional machining. To machine difficult-to-cut materials, thermally enhanced machining (TEM) has been developed internationally. One of the currently applied thermally enhanced machining methods, laser assisted machining (LAM), uses laser preheating to locally soften materials ahead of the cutting tool before machining. There have been no research works by LAM for three-dimensionally shaped specimens. Compared to a plate shape, it is more difficult to predict the optimum LAM preheating temperature for a three-dimensional shape, because with a 3D surface, the shape of the preheated spot changes continuously during machining. In this study, LAM was applied to spherical shaped specimens of three different materials, AISI 1045, Inconel 718 and titanium alloy for three dimensional machining. Before the machining experiments, thermal analysis was carried out by finite element analysis (FEA) to determine the optimum preheating temperature. A contouring machining method was used in the experiments. Cutting force and surface roughness were measured to analyze machining characteristics, and were found to be improved by LAM. These results can be applied to similar machining of difficult-to-cut materials.